Desain Primer Spesifik untuk Gen yang Berperan pada Biosintesis Beta Karoten Kelapa Sawit - Lollie A.P. Putri; Muhdi Muhdi; Meiriani Meiriani; Diana S (Jurnal Agrista, 2007)
Design in Specific Primer for Gen Controlling Beta Carotene Biosynthesis of Oil Palm ABSTRACT. The research towards increasing palm oil quality has received a great priority in compliance with high attentions for consumers to health and economic value of vegetable oil. The objective of experiment is to obtain specific primer and generate partial fragment gene having a role of increment in beta carotene biosynthesis of oil palm. Application of biomolecular technique in plant genetic engineering is believed to be able to accelerate the genetic gain. An effort to manipulate of carotene composition is basically modification in its biosynthetic enzymatic pathway. The approach primer designing PRIMER3 software was able to generate couple of primer Beta-F and Beta-R and produce fragment  of lycopene β-cyclase (578 bp). Success in construction of complete functional gene will be a base of creating oil palm varieties with improved palm oil quality in future.